2008
DOI: 10.1097/ijg.0b013e31815a34ac
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between Helicobacter pylori Infection or CagA-bearing Strains and Glaucoma

Abstract: Neither H. pylori infection nor seropositivity for virulent CagA-bearing H. pylori strains have significant association with the occurrence of glaucoma of any type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 22 publications
3
37
0
1
Order By: Relevance
“…In 2 subsequent studies, we reported: (1) a beneficial effect of H. pylori eradication on glaucoma progression, suggesting a possible causal link between the bacterium and glaucoma [5] , and (2) increased H. pylori-specific IgG antibody concentration in the aqueous humor of POAG patients, the concentration of which correlated with the degree of vertical cupping, possibly indicating the severity of glaucomatous damage [6] . Reports from other ethnic populations have also shown a relationship between glaucoma and H. pylori infection [7,8] , although this has not been confirmed by all the relevant studies published so far [9,10] , and thus this association may only apply to a limited subpopulation of glaucoma patients. Similar observations have been made in Korea, China, India, Turkey and Iran [8,11] .…”
Section: Introductionmentioning
confidence: 77%
“…In 2 subsequent studies, we reported: (1) a beneficial effect of H. pylori eradication on glaucoma progression, suggesting a possible causal link between the bacterium and glaucoma [5] , and (2) increased H. pylori-specific IgG antibody concentration in the aqueous humor of POAG patients, the concentration of which correlated with the degree of vertical cupping, possibly indicating the severity of glaucomatous damage [6] . Reports from other ethnic populations have also shown a relationship between glaucoma and H. pylori infection [7,8] , although this has not been confirmed by all the relevant studies published so far [9,10] , and thus this association may only apply to a limited subpopulation of glaucoma patients. Similar observations have been made in Korea, China, India, Turkey and Iran [8,11] .…”
Section: Introductionmentioning
confidence: 77%
“…In another study using the same method, Galloway et al found no relationship between H. pylori infection positivity and glaucoma (24) . Similarly, no relationship was found between glaucoma and H. pylori infection positivity in a study by Kurtz et al, in which serology and cytotoxin-associated geneA (CagA) seropositivity were evaluated (25) . Handa et al reported that the CagA gene may be associated with apoptosis, irregular gastric cell activity, and carcinogenesis (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Neither H. pylori infection nor seropositivity for virulent CagA-bearing H. pylori strains has significant association with the occurrence of glaucoma of any type (Kurtz et al, 2008). Eye color is one of the major racial and diagnostic features in anthropological studies and it is used to characterize differences between populations where certain authors have shown some associations between eye color *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%